The Effectiveness of Advocacy for Domestic Violence Victims from the Perspective of Maqasid al-Shari'ah - Yeni Kartikaningsih; Sachrawi Hidayat; Moh. Muhibbin; Nur Hasan; Mohammad Jindan Alfayed Dewa Filhaq (ISTIFHAM, 2026)
Domestic violence is a serious violation of human rights that requires an institutional response beyond just legal measures. The Population, Family Planning, and Women's Empowerment Agency (BKKBPP) of Malang City plays a strategic, legally mandated role in providing integrated support to victims of domestic violence through legal aid, psychological counseling, medical assistance, and mediation. This research evaluates how effective BKKBPP's advocacy is in protecting and empowering victims and assesses its consistency with Maqasid al-Shari'ah's normative goals. Using a normative-empirical juridical approach based on primary field data and Islamic family law literature, the study reveals that BKKBPP's advocacy functions across three interconnected areas: legal (both litigative and non-litigative), psychosocial (trauma counseling and rehabilitation), and social mediation. Results show that when these areas operate collaboratively and focus on victims, the agency's efforts significantly improve victims' safety, mental health, and social reintegration. Challenges include victims' reluctance to report, limited resources, scheduling conflicts, and the diversity of victim profiles. From the perspective of Maqasid al-Shari'ah, BKKBPP's advocacy supports core Islamic legal goals such as protecting life (hifz al-nafs), intellect (hifz al-'aql), progeny (hifz al-nasl), and dignity. This study adds to the literature by illustrating that institutional advocacy aligned with Maqasid al-Shari'ah is both Jurisprudentially sound and practically vital for fully protecting victims of domestic violence in a Muslim society.